Mobile application as teaching and learning tool to mute and deaf students / Mat Redhuan Samsudin and Rushana Sulaiman - Samsudin, Mat Redhuan; Sulaiman, Rushana (2022)
Education is the foundation for the development of intellectual human capital that can provide a more perfect life and can contribute to the development of society and produce competent national leaders. Formal education is given to the children for which they must get formal education in school. According to Hamdi Ishak, Ab Halim Tamuri, Rosadah Abdul Majid, and Safani Bari (2012) children born into this world are entitled to education in preparation for their lives in the future. Education should be given to students based on the abilities, talents, and capabilities of students so that it is in line with the wants, technology and needs of the students.